Coordinated Control of Distributed Three-And Single-Phase Inverters Connected to Three-Phase Three-Wire Microgrids - Brandao, Danilo I.; Araujo, Lucas S.; Alonso, Augusto M. S. [UNESP]; Dos Reis, Geovane L.; Liberado, Eduardo V. [UNESP]; Marafao, Fernando P. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2020)
This paper explores the coordinated strategy named power-based control (PBC) to properly coordinate grid-Tied single-And three-phase distributed energy resources (DERs) in three-phase three-wire microgrids (MGs). By means of a narrowband, low data rate communication, such strategy accommodates current-And voltage-controlled distributed inverters providing proportional sharing of active, reactive, and unbalanced (negative-sequence) power terms, also offering dispatchable power flow and high power quality (PQ) at the MG's point of common coupling (PCC). Regarding the current unbalanced compensation, a particular case considering two distributed single-phase inverters is discussed through mathematical analysis in terms of balanced and unbalanced power terms, and experimental results on which the PBC is applied to demonstrate that this strategy corroborates with Steinmetz principle. Finally, the complete strategy is evaluated in simulation considering the model of a real urban power distribution grid under typical operational conditions.
Keywords: Current-controlled mode (CCM); hierarchical control; microgrid (MG); power sharing; three-phase converters; unbalance compensation; voltage-controlled mode (VCM)